Origins and Evolution of the Primate Hepatitis B Virus - Locarnini, Stephen A.; Littlejohn, Margaret; Yuen, Lilly K. W. (Frontiers in Microbiology, 2021)
Recent interest in the origins and subsequent evolution of the hepatitis B virus (HBV) has strengthened with the discovery of ancient HBV sequences in fossilised remains of humans dating back to the Neolithic period around 7,000 years ago. Metagenomic analysis identified a number of African non-human primate HBV sequences in the oldest samples collected indicating that human HBV may have at some stage, evolved in Africa following zoonotic transmissions from higher primates. Ancestral genotype A and D isolates were also discovered from the Bronze Age, not in Africa but rather Eurasia, implying a more complex evolutionary and migratory history for HBV than previously recognised. Most full-length ancient HBV sequences exhibited features of inter genotypic recombination confirming the importance of recombination rather than the mutation rate of the error-prone viral replicase as the main driver for successful HBV evolution. A model for the origin and evolution of HBV is proposed which includes multiple cross-species transmissions and favours subsequent recombination events in order to provide the selective advantage of successful transmission and persistent infection in the primate host.